2005
DOI: 10.1016/j.biopsych.2005.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic drugs elevate mRNA levels of presynaptic proteins in the frontal cortex of the rat

Abstract: We found an increase in the transcription of genes coding for proteins involved in synaptic plasticity and synaptic activity in the FC. We furthermore found that the gene expression profile of APDs is different between FC and striatum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
45
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 74 publications
(89 reference statements)
8
45
0
Order By: Relevance
“…First, limited sample size makes it difficult to determine significant drug effect when comparing treated versus untreated subjects or correlating APD treatment with gene expression. In addition, chronic APD treatment is thought to induce long term cellular and neuroadaptive changes that would influence gene expression (Hyman and Nestler 1996;MacDonald et al 2005). Precedence for persisting drug effects exists in the dopamine system literature, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…First, limited sample size makes it difficult to determine significant drug effect when comparing treated versus untreated subjects or correlating APD treatment with gene expression. In addition, chronic APD treatment is thought to induce long term cellular and neuroadaptive changes that would influence gene expression (Hyman and Nestler 1996;MacDonald et al 2005). Precedence for persisting drug effects exists in the dopamine system literature, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…326 Microarray studies in rats treated with clozapine or haloperidol found an increase in the transcription of genes coding for proteins involved in synaptic plasticity and activity in the frontal cortex. 327 Different gene upregulation profiles were observed after clozapine and haloperidol treatment in two separate studies by the same team of investigators. 328,329 Interestingly, these studies found that Synapsin II, a gene implicated in schizophrenia, was upregulated by haloperidol, and the glucose-dependent insulinotropic polypeptide (GIP), a gene that may have a role in glucose intolerance and weight gain, was upregulated by clozapine.…”
Section: Discerning the Mechanism Of Action Of Antipsychoticsmentioning
confidence: 99%
“…Previous similar microarray studies investigating the effects of chronic administration of antipsychotics in brains of rodents are limited and yet informative (Chen and Chen, 2005;Chong et al, 2002;Kontkanen et al, 2002;MacDonald et al, 2005;Thomas et al, 2003). Chong et al (2004) showed that chronic administration of clozapine in rats for 28 days upregulated mRNA and protein for rat glia-derived nexin in brains of exposed animals.…”
Section: Introductionmentioning
confidence: 99%
“…The authors showed that both drugs increased genes associated with lipid metabolism, such as apolipoprotein D, the mouse homolog of oxysterol-binding protein-like protein 8, and lysophosphatidic acid acyltransferase (Thomas et al, 2003). MacDonald et al (2005) investigated gene profiles in the frontal cortex and striatum of rats in response to chronic exposure to haloperidol and clozapine. Several genes coding for presynaptic proteins including VAMP1, syntaxin 1A, and SNAP 25 were upregulated in the frontal cortex, potentially increasing synaptic plasticity and synaptic activity (MacDonald et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation